2017
DOI: 10.1097/md.0000000000006063
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening bleeding from gastric mucosal angiokeratomas during anticoagulation

Abstract: Rationale:Angiokeratomas are the earliest manifestation of Fabry disease (FD), and the extent of their appearance is related to disease severity. Angiokeratomas are mostly found on cutaneous regions.Patient concerns, diagnoses, interventions, and outcomes:Here we report an FD patient with widespread gastrointestinal angiokeratomas who developed life-threatening bleeding following anticoagulation for atrial fibrillation.Lessons:Careful observation for gastrointestinal bleeding is warranted for patients on antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Serpins are known to play a role in coagulation, and loss of serpins might induce a variety of bleeding disorders (Kaiserman et al, 2006 ). It has recently been shown that angiokeratoma, one of the first dermatologic disease presentations in Fabry patients, if present in gastrointestinal mucosa can lead to life-threatening bleeding episodes during coagulation therapy (Oh et al, 2016 ; Kang et al, 2017 ). Interestingly, 30% of Fabry patients show cerebral microbleeds (Kono et al, 2016 ), which together with the downregulated Thrombospondin 1 (Thsd7a) and Thromboxane a2 receptor (Tbxa2r) can be related to a general deficit in blood coagulation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Serpins are known to play a role in coagulation, and loss of serpins might induce a variety of bleeding disorders (Kaiserman et al, 2006 ). It has recently been shown that angiokeratoma, one of the first dermatologic disease presentations in Fabry patients, if present in gastrointestinal mucosa can lead to life-threatening bleeding episodes during coagulation therapy (Oh et al, 2016 ; Kang et al, 2017 ). Interestingly, 30% of Fabry patients show cerebral microbleeds (Kono et al, 2016 ), which together with the downregulated Thrombospondin 1 (Thsd7a) and Thromboxane a2 receptor (Tbxa2r) can be related to a general deficit in blood coagulation pathways.…”
Section: Discussionmentioning
confidence: 99%